Hepatitis B: The view from West Africa - Mario Lepore; Harr F. Njai; Deborah A. Garside; Yusuke Shimakawa; Mary M.E. Crossey; Ramou Njie; Maud Lemoine (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2015)
The Prevention of Liver Fibrosis and Cancer in Africa (PROLIFICA) study began in 2011 in The Gambia, Sénégal and Nigeria. The study aims to reduce the risk of hepatocellular carcinoma (HCC) in West Africa through the suppression of the Hepatitis B virus (HBV). The biological samples collected allow for the detection of novel liver cancer biomarkers in the hope of improving the diagnostic ability of early disease states. The PROLIFICA platform hopes to improve cancer diagnostics whilst simultaneously providing the training, skills and infrastructure necessary to develop the quality of liver cancer care in West Africa.